Efektivitas Pengelolaan Ruang Terbuka Hijau Wisdom Park UGM bagi Pemulihan Urban Stress di Yogyakarta - Arfani, Rissa; Trimarstuti, Jeki (PT Penjaminan Infrastruktur Indonesia (Persero), 2024)
The high population density in Yogyakarta has led to various economic issues and serves as an indicator of the rising level of depression in the Province of DIY. Urban facilities like Green Open Spaces (GOS) offer a potential means to reduce urban stress in the city. However, the GOS standards as a solution for urban stress recovery often do not align with current regulations. This study aims to assess the effectiveness of GOS at Wisdom Park UGM in mitigating urban stress among Yogyakarta residents. Using a quantitative approach, the research findings are presented deductively and descriptively. The results of the analysis highlight the potential and problems of each research aspect. The variables observed here are the goals of the visitors’ activities, the effectiveness of GOS management (including vegetation, cleanliness, design, infrastructure, and accessibility), and urban stress recovery activities within the research locus, based on a survey of 100 respondents aged 15 to 64 years old. The findings indicate that Wisdom Park UGM is fairly effective as a GOS to restore urban stress. The park’s strengths include the diversity of vegetation and fauna, convenient access via various transportation modes, affordable entry fees, and a comprehensive range of supporting activities and facilities.